MEMAHAMI WARISAN BUDAYA DAN IDENTITAS LOKAL DI INDONESIA - Indrawati, Mamik; Ifana Sari, Yuli (Jurnal Penelitian dan Pendidikan IPS, 2024)
Indonesia, with its abundant cultural diversity, is fertile ground for understanding cultural heritage and local identity. From Aceh to Papua, every region in Indonesia exudes unique cultural richness. Indonesia has a rich tribal culture that is spread widely throughout the islands of this country so that the diversity of tribes and races in Indonesia has led to the formation of various cultures. This article is to provide a better insight into the richness of Indonesian culture and explore various efforts to preserve local identity that have been undertaken by the government, NGOs and civil society in Indonesia. The research methods used include collecting data, analyzing information, and compiling findings. The initial step in this research is to conduct a literature study on the topic being researched. Through searches in academic databases and other sources, relevant literature on cultural heritage, local identity and Indonesia will be collected. Journal articles, books, research reports, and online sources will be used to gain a comprehensive understanding of the topic. The results of this research highlight the importance of understanding and preserving cultural heritage and local identity in Indonesia. With concrete steps, such as empowering local communities and implementing supportive policies, Indonesia can maintain its extraordinary cultural wealth and strengthen local identity in facing the challenges of globalization and modernization. Cultural heritage and local identity have a very important role in shaping the social, cultural and political framework in Indonesia. Abundant cultural riches, ranging from art, music, dance, language, to traditional traditions, reflect the diversity and uniqueness of Indonesian society. Local identity plays a central role in forming community unity and strengthening solidarity and a sense of pride in local culture. Â